Psikoedukasi Pengelolaan Stres Kerja untuk Meningkatkan Optimisme melalui Media Pocket Book pada Pegawai Badan Narkotika Nasional Provinsi Sumatera Selatan - Jeniffer Mina Claudia Ongge; Rina Oktaviana (Yayasan Kawanad, 2026)
The South Sumatra Provincial National Narcotics Board (BNNP) is a government institution responsible for implementing programs related to the Prevention and Eradication of Drug Abuse and Illicit Trafficking (P4GN). In carrying out administrative duties and public services, employees are required to maintain professionalism, discipline, and productivity while dealing with various work demands. This community service activity aimed to provide psychoeducation on work stress management, work motivation, and optimism through a pocket book for employees of BNNP South Sumatra. The activity involved 13 employees and was conducted through the distribution and use of a pocket book containing practical information, motivational messages, stress management strategies, and simple relaxation techniques. The activity was evaluated through observation and participant feedback during the implementation. The results showed positive responses from participants, including greater participation in discussions, increased interest in the materials, and more open sharing of work-related experiences. Participants also reported that the pocket book provided useful reminders for maintaining motivation and a positive perspective when dealing with work demands. The activity indicates that a pocket book can serve as a practical psychoeducational medium to support work motivation, stress management, and optimism among employees.